Impact of fibrinogen levels and modified Glasgow prognostic score on survival of stage III/N2 non-small cell lung cancer patients treated with neoadjuvant therapy and radical resection - Katharina Sinn; Berta Mosleh; Michael Grusch; Walter Klepetko; Konrad Hoetzenecker; Thomas Klikovits; Daniela Gompelmann; Mir Alireza Hoda (BMC Cancer, 2022)
Abstract Purpose The prognostic value of pretreatment and preoperative fibrinogen plasma levels and the modified Glasgow prognostic score (mGPS) in stage III/N2 non-small cell lung cancer (NSCLC) patients who receive neoadjuvant treatment followed by radical surgery is yet unclear. Methods Fibrinogen levels and mGPS of 84 patients with initial stage III/N2 NSCLC, who received neoadjuvant therapy followed by complete surgical resection from 2002 to 2014 were retrospectively analyzed and correlated with clinical parameters and overall survival (OS). Data were analyzed using log-rank and Cox regression analysis adjusted for clinical and pathological factors. Results Median serum fibrinogen level after neoadjuvant treatment was 439 mg/dL (IQR 158 mg/dL). Elevated fibrinogen levels (> 400 mg/dL) after neoadjuvant treatment were significantly associated with poorer OS (28.2 months vs. 60.9 months, HR 0.562, p = 0.048). Importantly, a decrease in fibrinogen levels after neoadjuvant treatment (n = 34) was found to be an independent predictor for favorable OS in multivariate analysis (HR 0.994, p = 0.025). Out of 80 patients, 55, 19 and 6 patients had a mGPS of 0, 1 and 2, respectively. Moreover, elevated mGPS after neoadjuvant treatment (mGPS 1–2) showed a non-significant trend for poorer OS compared to mGPS 0 (28.2 vs. 46.5 months, HR 0.587, p = 0.066). Conclusion Elevated fibrinogen levels after neoadjuvant therapy prior to surgery in stage III/N2 NSCLC patients are associated with significant disadvantage for OS. A decrease in fibrinogen levels after neoadjuvant therapy was found to be a predictor for superior OS in this retrospective patient cohort.